2009
DOI: 10.3168/jds.2008-1425
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of pregnancy effect on milk, fat, and protein yields of Canadian Ayrshire, Jersey, Brown Swiss, and Guernsey breeds

Abstract: Pregnancy has a negative impact on milk production in dairy cattle. Estimates of the effects of pregnancy are required in genetic evaluation models. Test-day records of Ayrshire, Jersey, Brown Swiss, and Guernsey breeds were analyzed phenotypically for the effect of pregnancy using 4 different models. Milk, fat, and protein yields were analyzed separately. The first model used a fourth-order Legendre polynomial regression on days in milk within classes of 10 d open. The second model fitted stage of pregnancy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 18 publications
4
36
0
Order By: Relevance
“…In all cases, average lactations were more than 165 d longer than the traditional 305-d lactation in cows calving at intervals of 12 mo. High-yielding dairy cows are capable of lactations well beyond 400 d (Osterman and Bertilsson, 2003;Kolver et al, 2006;Auldist et al, 2009;Madsen et al, 2008;); however, dairy cows under intensive management lactate until milk secretion is drastically reduced by the advanced stage of gestation (Loker et al, 2009). Therefore, length of lactation is almost completely determined by length of calving interval.…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, average lactations were more than 165 d longer than the traditional 305-d lactation in cows calving at intervals of 12 mo. High-yielding dairy cows are capable of lactations well beyond 400 d (Osterman and Bertilsson, 2003;Kolver et al, 2006;Auldist et al, 2009;Madsen et al, 2008;); however, dairy cows under intensive management lactate until milk secretion is drastically reduced by the advanced stage of gestation (Loker et al, 2009). Therefore, length of lactation is almost completely determined by length of calving interval.…”
Section: Resultsmentioning
confidence: 99%
“…Regard to the relation between DO classes and TMY, Alemam (2002) demonstrated partial linear and quadratic regression coefficients of DO on TMY with highly significant effect. Also, Loker et al (2009) indicated that milk production for cows with DO ≤180 tended to have low yields in the last part of lactation. Cows with longer DO, however, had proportionally higher milk yield throughout lactation, suggesting a possible confounding effect of production level with DO effects.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Stadnik et al (2017) point out that reproduction and milk yield traits had negative correlations throughout lactation. Loker et al (2009) reported prolonged DO in cows with relatively higher milk yield. Similarly, Heuer et al (1999) emphasized that higher first test day milk yield indirectly dropped fertility performance of dairy cows.…”
Section: Introductionmentioning
confidence: 99%